2016
DOI: 10.2139/ssrn.2773455
|View full text |Cite
|
Sign up to set email alerts
|

Superior Bargaining Power and the Global Food Value Chain: The Wuthering Heights of Holistic Competition Law?

Abstract: In this paper we analyse the role of superior bargaining power in competition law and policy in the agri-food value chain. Conventional approaches to competition law based on a neoclassical price theory perspective tend to neglect or to stay opaque on the role of bargaining power in competition law. However, national competition authorities and national legislators seem to be less biased by specific theoretical approaches and have increasingly engaged with the application of the concept of bargaining power in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Bonnet and Zohra (2015), using a model of Draganska et al (2010), observe that value added created by organic label in the French fluid milk market helped to balance bargaining power along the supply chain. Lianos and Lombardi (2016) use a holistic approach in the Global Value Chain framework. They examine market power and concentration through the vertical links between in the chain to understand if and how lead actors can capture value.…”
Section: Imperfect Price Transmission Along the Food Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonnet and Zohra (2015), using a model of Draganska et al (2010), observe that value added created by organic label in the French fluid milk market helped to balance bargaining power along the supply chain. Lianos and Lombardi (2016) use a holistic approach in the Global Value Chain framework. They examine market power and concentration through the vertical links between in the chain to understand if and how lead actors can capture value.…”
Section: Imperfect Price Transmission Along the Food Chainmentioning
confidence: 99%
“…On the contrary, cooperatives with high market share may discriminate between buyers. In their recent paper, Lianos and Lombardi (2016) acknowledge the different anti-trust policies of the USA and the EU: while cooperatives benefit from anti-trust immunity in the USA, the policy setting in Europe is much more complex and difficult to interpret.…”
Section: Policy Instruments and Market Powermentioning
confidence: 99%
“…Gorton et al (2015) also employed a quantitative analysis to study UTPs in food supply chains in the USA and confirmed that trustworthiness was positively related to fair practices. Using a Global Value Chain framework, Lianos and Lombardi (2016) provided a theoretical framework to examine food value chains in contrast to competition law. Sexton (2017) identified three main approaches and four types of methodologies for empirical investigations of trading practices (interpretive methodologies based on interviews; surveys, either online, by phone, or face to face; case studies; modelling).…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…In that respect, differences between monopoly power and bargaining power, the subject of an increasingly active discussion amongst economists and lawyers specializing in antitrust policies (Shastitko and Pavlova, 2017a;Lianos and Lombardi, 2016) provides elements to discuss alternative governance mechanisms as well as regulatory involvement of antitrust authorities in organizing transactions between two interdependent entities.…”
Section: A Different Perspectivementioning
confidence: 99%